Обґрунтування господарських рішень, що впливають на інвестиційну привабливість підприємства - Ларка, Людмила Сергіївна (НТУ "ХПІ", 2017)
Визначено особливості планування комплексу господарських рішень, що впливають на рівень інвестиційної привабливості підприємства. Систематизовано комплекси рішень, що забезпечують цільовий рівень інвестиційної привабливості підприємства. Наведено вимоги до оцінювання інвестиційної привабливості підприємства. Проаналізовано основні види інвестиційної привабливості. Показані цілі формування інвестиційної привабливості. Запропоновано критерії оцінювання ефективності рішень з підвищення ділової активності підприємства, підвищення прибутковості інвестиційної діяльності, підвищення конкурентоспроможності продукції підприємства, оптимізації організаційної структури, удосконалення матеріально-технічного забезпечення, використання основних фондів тощо.

Specific features of planning a complex of economic decisions that affect the level of investment attractiveness of the enterprise are determined. The purpose of the article is to formulate the main complexes of economic decisions influencing investment attractiveness on the basis of an analysis of the theoretical aspects of the company's investment attractiveness and to propose a methodical approach to justify their effectiveness. Complexes of solutions that provide the target level of investment attractiveness are systematized. It is determined that one of the most significant indicators that affect the investment attractiveness of an enterprise is the percentage of innovative products in its strategic business portfolio. The requirements for estimating the investment attractiveness of the enterprise are given. The main types of investment attractiveness are analyzed. The purposes of formation of investment appeal are shown. The criteria for assessing the effectiveness of decisions to improve the business activity of the enterprise, increase the profitability of investment activities, competitiveness of enterprise products, optimize the organizational structure, improve the material and technical supply, use fixed assets, etc.
Substantiation of economic decisions affecting the investment attractiveness of an enterprise
Keywords: комплекс рішень; прибутковість; конкурентоспроможність; інноваційна політика; ділова активність; complex of solutions; profitability; competitiveness; innovation policy